The People of Dhimmah and their Political Opposition Activites in the Kurdish Countries in the Abbasid Era (132-334A.H\750-945A.D) - Khasro Jabbar Abddulla; Ahmed Mrza Merza (Zanco Journal of Humanity Sciences)
Many religious groups and Kurdish tribes, until the middle of the third century AH / ninth century AD, adhered to their ancient religious beliefs of the Kharami, rich, Christianity and Judaism in the country of the Kurd, and these until that time with their population density constituted most of the Kurdish social fabric, the appearance of their religious culture, and the pillar of their agricultural, pastoral, craft and commercial economy, and thus they were an important and vital part of the Kurdish-Islamic society, and according to these considerations and according to considering Islamic political jurisprudence with great responsibility. However, from one to another, part of them, especially religious groups and influential tribes, carried out opposition political activities and military movements against the Abbasid state. Some of these opposition activities were the resulted from motives Religious-political-historical, it rejected Islam as a religion and authority in principle, and it was on two levels, the level of leadership, religious elites, and the level of the grassroots. At the first level, the motives were in general, maintaining religious influence, social status, economic interests and political aspirations. At the grassroots level, the motives were in general, religious beliefs and feelings, and their commitment to obedience to the tribal leader and the cleric, and in general, it was in one of its forms, an expression of the adherence to part of the Kurds to their old religious identity.While other opposition positions to another section of the dhimmi people in the country of the Kurds, were caused by the arbitrary and harsh decisions of the authority against them, especially the decisions that related to the issue of excess, taxes, tribute, and methods of collecting them, or because of them were arbitrariness, greed and personal greed for some states and leaders in some states of the Kurds, who were forcing people to pay additional percentages of taxes, and exploiting their positions for that and to satisfy their satiation of money and property.This type of opposition and religious movements resulted in orders, including what was immediate and temporary; such as human losses and destruction in the Kurdish areas in which these movements broke out, and the destruction of the economy, in addition to the cultural and civilizational isolation of these groups from their Islamic environment in general, and their Kurdish-Muslim surroundings in particular, and sometimes it was the cause of a clash between the Muslim part of it and the other non-Muslim section, including what was the consequences of the return of the term; them caused the influential Kurdish elites not to reach the center of the administration and decision in the capital of the Caliphate Baghdad, and their stay on the sidelines of events, unlike the Turks, who were able to reach, respectively. To the decision center in Baghdad and control its management, as well as the naive religious feeling was a reason for the ease of containing these religious and tribal groups, by various political theories, and a reason for the waste of their human and economic potential.Religious conflict usually has catastrophic results and its effects are deep and continuous, especially on the weaker side, and the conflict in it is zero, in the sense that each of the parties to the conflict is trying to eliminate its opponent once and for all, so the position of the Abbasid state towards these movements was cruel and violent.